Factors affecting chemical literacy and achievement of high school students - Alumaga, Marie Jessica B. (2008)
This study aimed to determine the relationship between chemical literacy, chemistry achievement, and the factors students' abilities, characteristics, and background. The study used Chemical Literacy Questionnaires, Preconception Checklist, Study Habits Questionnaire, Parental Involvement Scale, Attitude Toward Chemistry Questionnaire and Chemistry Achievement Test, which were administered to fourth year high school students enrolled in science and regular public high schools in Cavite, Laguna, and Batangas. It was found that students enrolled in the science curriculum performed better in all levels of chemical literacy than other students. All levels of chemical literacy are significantly related to achievement in chemistry. Some factors such as curriculum, mathematical ability, reading comprehension, and attitude toward chemistry can be used to predict the students' level of chemical literacy and achievement.